Pendampingan Pengembangan Aplikasi Etakon Desa Tegal Wangi Kabupaten Cirebon - Raditya Danar Dana; Fadhil Muhammad Bsysyar; Agus Bahtiar (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Tegal Wangi Village is a partner location in this service. A case that often occurs in this village is difficulty in accessing health information and education services. The Tegal Wangi Village community has long faced obstacles in obtaining relevant information regarding their health conditions, especially when it comes to questions about their health conditions. Apart from that, educational issues are also the focus of this service, with gaps in access to education affecting the understanding and knowledge of the people in this village. Based on the discussion of community service that has been described, then the conclusion with the theme "Assistance in the Development of the Etakon Application in Tegal Wangi Village, Cirebon Regency" is as follows. The Tegal Wangi Village website is successful implemented using the 5 stages of the Waterfall model, namely planning, analysis, design, implementation and testing. Planning was carried out by collecting data, which resulted in 4 functional requirements and 2 user access. Web page design using the Data Flow Diagram model. Database design using the Entity model Relationship Diagrams. The implementation phase is carried out using the Laravel framework with a Model, View and Controller based development scheme. The application that has been built has been tested using the black box testing method in accordance with the user's access rights. Based on the results of black box testing, it can be seen that the expected results from testing items and deleting data are valid scenarios. Then, community service activities can help village officials become digitally literate in accordance with the target of Cirebon district.